Clinical Satisfaction and Quality of Ceramic Fixed Dentures - Goiato, Marcelo Coelho [UNESP]; Pesqueira, Aldieris Alves [UNESP]; Monteiro, Douglas Roberto; de Faria Almeida, Daniel Augusto; Santos, Daniela Micheline dos [UNESP] (Wiley, 2013)
It is known that several factors can affect the clinical success and durability of fixed partial dentures. Therefore, the aim of the present study was to present a literature review about the longevity, clinical success, and quality, as well as, patients' and dental surgeons' satisfaction of ceramic fixed dentures. High rate of patients' satisfaction has been observed in relation to the esthetic of ceramic crowns. In addition, the literature has shown that dental ceramics can be used in several clinical situations with high success rate and longevity. Despite of failures and complications of ceramic restorations, nowadays, with the improvement of mechanical properties of such materials, ceramic crowns present a favorable prognosis and can be used in several clinical situations with high success rate, clinical quality, and great patients' satisfaction. © 2013 The American Ceramic Society.